2021
DOI: 10.1073/pnas.2101596118
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo selection-derived d -peptide for engineering erythrocyte-binding antigens that promote immune tolerance

Abstract: Significance Erythrocyte-bound antigens can drive immune tolerance in an antigen-specific fashion. Exploiting this phenomenon, we developed a general strategy to promote antigen-specific tolerance by engineering peptide and protein antigens to bind erythrocytes. Here, we showed that a fully d -chiral peptide library can be selected in vivo for the de novo discovery of a robust erythrocyte binder, which we attached to peptide and protein antigens. An administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Affinity selection–mass spectrometry (AS–MS) techniques have traditionally been used to probe protein–protein interactions in vitro . Our group has recently shown that chemical libraries may reach the diversity of other display techniques for identification of peptide binders to proteins, and that this strategy can be applied for cell-surface selection in vivo . In this work, we have added an additional spatial element to this strategy by extracting the cytosol for in-cell selection of fully synthetic peptide libraries conjugated to a model antisense cargo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Affinity selection–mass spectrometry (AS–MS) techniques have traditionally been used to probe protein–protein interactions in vitro . Our group has recently shown that chemical libraries may reach the diversity of other display techniques for identification of peptide binders to proteins, and that this strategy can be applied for cell-surface selection in vivo . In this work, we have added an additional spatial element to this strategy by extracting the cytosol for in-cell selection of fully synthetic peptide libraries conjugated to a model antisense cargo.…”
Section: Discussionmentioning
confidence: 99%
“…34 Our group has recently shown that chemical libraries may reach the diversity of other display techniques for identification of peptide binders to proteins, 33 and that this strategy can be applied for cell-surface selection in vivo. 42 In this work, we have added an additional spatial element to this strategy by extracting the cytosol for in-cell selection of fully synthetic peptide libraries conjugated to a model antisense cargo. By comparing these sequences to those found in a whole cell extract, we can exclude sequences that accumulate in the endosomes.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Our group has recently shown that chemical libraries may reach the diversity of other display techniques for identification of peptide binders to proteins 27 , and that this strategy can be applied for cell-surface selection in vivo. 36 In this work, we have added an additional spatial element to this strategy, by extracting the cytosol for in-cell selection of fully synthetic peptide libraries conjugated to a model antisense cargo. By comparing these sequences to those found in a whole cell extract, we can exclude sequences that accumulate in the endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently demonstrated that in vivo affinity selection-mass spectrometry (AS-MS) could identify an erythrocyte-targeting D-peptide. 36 Such label-free techniques applied to the cell surface can be used to discover novel, non-canonical, D-peptide binders without the addition of display scaffolds or encoding tags.…”
Section: Introductionmentioning
confidence: 99%